Injertos. - Composición de cinco obras musicales que fusionan el Sanjuanito y el Albazo con el Jazz y la Bossanova, empleando técnicas de composición tanto clásicas como contemporáneas - Guerrón Gómez, Edison Rodrigo (2025)
Injertos is an artistic proposal that consists of the creation of five musical compositions where I fuse traditional Ecuadorian genres, such as sanjuanito and albazo, with influences from jazz and bossa nova. These works combine classical and contemporary composition techniques, with the aim of contributing to the preservation and diffusion of Ecuadorian musical folklore, while exploring new sounds through interaction with genres of great rhythmic and harmonic complexity. The main purpose of this project is to broaden the scope of traditional Ecuadorian music, adapting it to current formats without losing its cultural essence. To do so, I have thoroughly investigated the structure, form, rhythm and harmony of the selected genres, achieving a fusion that respects both the identity of sanjuanito and albazo, as well as the characteristic elements of jazz and bossa nova. The compositions are designed for an instrumental ensemble consisting of piano, guitar, violin, viola, trumpet, alto saxophone and bass/contrabass, instruments that are part of the musical tradition in various regions of Ecuador. In addition, I used music notation technologies through specialized software to develop and present the arrangements. Through this interdisciplinary approach, I seek to generate innovative fusion music repertoire that can be performed by new ensembles, propelling Ecuadorian music into a globalized context